Novel linear switched-flux PM machine with 9/10 primary/secondary pole number combination. Issue 6 (2nd November 2015) - Lu, Qinfen; Li, Yanxin; Ye, Yunyue; Chen, J.T.; Zhu, Z.Q.
Abstract : Purpose: – Due to linear structure, linear switched flux permanent magnet machines (LSFPMMs) also may have odd pole primary, such as 9, 15, 21, etc., without unbalanced magnetic force in equivalent rotary machines. The paper aims to discuss these issues. Design/methodology/approach: – In order to increase the thrust force density, the influence of some major design parameters, including split ratio, PM thickness, primary slot width and secondary pole width, are investigated by finite element analysis. For reducing the thrust force ripple under on-load condition, the end auxiliary teeth are adopted and their positions are also optimized. Findings: – This novel 9/10 primary/secondary poles LSFPMM has high average thrust force and low thrust force ripple by optimization. The results demonstrate that the odd pole primary may be a good candidate for long-stroke linear direct drive application. Originality/value: – A novel 9/10 primary/secondary poles linear switched flux permanent magnet machine is developed in this paper. The similar conclusions could be obtained for other LSFPMMs with odd pole primary.